PELAKSANAAN PERLINDUNGAN HUKUM TERHADAP AHLI WARIS DALAM PENYELESAIAN KLAIM PADA PERUSAHAAN ASURANSI JIWA PT. SUN LIFE FINANCIAL INDONESIA DI PEKANBARU - Nicolas Hutabarat; Rika Lestari; Setia Putra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
Implementation of submitting life insurance claims by heirs to PT. Sun Life FinancialIndonesia in Pekanbaru often happens when the insured submits a claim to the insurancecompany and it is not always accepted because there are things that cause the application tobe rejected, namely related to the results of investigations that are less transparent inproviding reasons and grounds for rejection, therefore the aim of the research Firstly, to findout the implementation of legal protection for heirs regarding heir rights at the life insurancecompany PT Sun Life Financial Indonesia in Pekanbaru. Second, to find out the legal effortsof heirs regarding heir rights at the life insurance company PT Sun Life Financial Indonesiain Pekanbaru.The research method in this thesis uses a type of sociological legal research, namelyresearch on the effectiveness of law in society. The nature of this thesis research isdescriptive research that systematically describes the facts and characteristics of the objectbeing studied accurately. The data collection technique in this research is the interviewmethod and literature review, then after the data is collected it is then analyzed to drawconclusions.Based on research conducted, legal protection for heirs regarding heir rights at the lifeinsurance company PT Sun Life Financial Indonesia in Pekanbaru is not in accordanceviolates Article 31 verses 3 and 4 law Number 40 of 2014 concerning Insurance because inprinciple the company should provide protection and comfort to customers and be open inproviding information regarding rejection of life insurance claims. The legal action taken bythe heirs regarding their rights to the life insurance company PT Sun Life FinancialIndonesia in Pekanbaru is difficult to take because the rejection of the life insurance claim isfinal and from the inaccurate results of the investigation the company is freed from itsobligation to provide compensation and does not accept criticism from heirs because theresults of the investigation cannot be contested. Meanwhile, if you take the non-litigationroute or mediation outside the court, it still cannot be done because PT. Sun Life FinancialIndonesia in Pekanbaru has not registered its company with the membership of an officialindependent institution under the OJK (Financial Services Authority), in this case thecompany certainly violates Article 54 of the 2014 Insurance Law which requires insurancecompanies to become independent and impartial institutions.